2014
DOI: 10.1371/journal.pone.0107896
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Force Spectroscopy Experiments on Galacturonic Acid Oligomers

Abstract: Pectins, forming a matrix for cellulose and hemicellulose, determine the mechanics of plant cell walls. They undergo salient structural changes during their development. In the presence of divalent cations, usually calcium, pectins can form gel-like structures. Because of their importance they have been the subject of many force spectroscopy experiments, which have examined the conformational changes and molecular tensions due to external forces. The most abundant unit present in the pectin backbone is polygal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 28 publications
(35 reference statements)
1
10
0
Order By: Relevance
“…One of the pioneering studies has produced evidence that for pectin (from citrus, purchased from Sigma) a two‐step transition of GalA units occurs from chair via boat to inverted chair (Marszalek et al., 2002). This finding was further confirmed by DFT simulations of galacturonic acid oligomers stretching (Cybulska et al., 2014). Force spectroscopy was also used to study the complexing mechanism of pectins, with other biomolecules, like the tumor signaling molecule Galectin‐3 (Gunning et al., 2009) and β‐lactoglobulin (Loveday & Gunning, 2018).…”
Section: Evaluation Of Pectin Conformationsupporting
confidence: 52%
See 1 more Smart Citation
“…One of the pioneering studies has produced evidence that for pectin (from citrus, purchased from Sigma) a two‐step transition of GalA units occurs from chair via boat to inverted chair (Marszalek et al., 2002). This finding was further confirmed by DFT simulations of galacturonic acid oligomers stretching (Cybulska et al., 2014). Force spectroscopy was also used to study the complexing mechanism of pectins, with other biomolecules, like the tumor signaling molecule Galectin‐3 (Gunning et al., 2009) and β‐lactoglobulin (Loveday & Gunning, 2018).…”
Section: Evaluation Of Pectin Conformationsupporting
confidence: 52%
“…The overall conformation of the HG chain is determined by the relative orientation of the GalA monomers at the glycosidic linkage (Figure 2b). The linkage geometry, that is the torsion of the monomers along the chain allows for the formation of a number of regular helical conformations separated by a relatively low transition energy (Cybulska, Brzyska, Zdunek, & Woliński, 2014; Pérez, Mazeau, & Hervé du Penhoat, 2000). Molecular modeling showed that four conformations of chains are possible: right (3.1) and left (3.2) handed three‐fold helices, a two‐fold helix (2.1), and a right‐handed four‐fold helix (4.1) (Pérez et al., 2000), which may differ in their cross‐section dimensions as visualized in Figure 2b for 3.1 versus 2.1 conformations.…”
Section: The Secondary Structure Of Pectin Chainsmentioning
confidence: 99%
“…This is confirmed by our earlier work on forced conformational transitions in various systems -not only for saccharides. [18,20,23] A typical EGOh for carbohydrate monomers usually displays a single energy maximum related to the structure being a good guess for the transition state (TS) searching procedure. Such TS can be treated as a specific linker between the starting and final EGO structures.…”
Section: Mono-and Disaccharidesmentioning
confidence: 99%
“…[18] Moreover, the type of the conformational conversion can also depend on the pyranose ring position in the oligosaccharide chain. [19,20] That is why the two types of monomeric: A (with the terminal glycosidic atoms in the position 1 and 3) and B (with the terminal glycosidic atoms in the position 1 and 4), dimeric: AB and BA (see Figure 1), trimeric: ABA and BAB etc. up to hexameric: ABABABA and BABABAB forms were considered here.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation